Efektifitas Anti Inflamasi Formulasi Kunyit (Curcuma Longa), Daun Binahong (Anredera Cordifolia) Dan Daun Sambiloto (Andrographis Paniculata) Terhadap Luka Sayat Pada Kelinci - Kh Endah Widhi Astuti; Sih Rini Handajani (Interest : Jurnal Ilmu Kesehatan, 2018)
Background: Perineal lacerations are tears that occur in the perineum because of the second stage of labor. The Javanese people do the purpose of this study is the effectiveness of anti-inflammatory formulation of turmeric (curcuma longa), leaves of Binahong (Anredera cordifolia) and leaves of Sambiloto (Andrographis paniculata) against incisions in rabbits. Method: The method used in this study is the method in this study. This research uses a quantitative method with a type of pure treatment research in the form of pre-post test design. The sample in this study was 10 rabbits per group in 5 groups. Results: There was an anti-inflammatory effect of the turmeric formulation, binahong leaves of bitter leaf (F1, F2 and F3) in the incision wound in rabbits (ρ <0.001). There is an anti-inflammatory effect of turmeric formulation, binahong leaves of bitter leaf on leukocyte levels in rabbit incisions in F1, F2 and F3 compared to the control group (ρ <0.001). Conclusion: Turmeric formula, binahong leaf, bitter leaf (F1, F2 and F3) in the incision in rabbits can improve the wound healing process.